The Impact of Probiotic Supplementation on Cognitive, Pathological and Metabolic Markers in a Transgenic Mouse Model of Alzheimer’s Disease - Webberley, Thomas S.; Masetti, Giulia; Bevan, Ryan J.; Kerry-Smith, Joshua; Jack, Alison A.; Michael, Daryn R.; Thomas, Sophie; Glymenaki, Maria; Li, Jia; McDonald, Julie A. K.; John, Daniel; Morgan, James E.; et al. (Frontiers in Neuroscience, 2022)
Brain degenerative disorders such as Alzheimer’s disease (AD) can be exacerbated by aberrant metabolism. Supplementation with probiotic bacteria is emerging as a promising preventative strategy for both neurodegeneration and metabolic syndrome. In this study, we assess the impact of the Lab4b probiotic consortium on i) cognitive and pathological markers of AD progression and ii) metabolic status in 3xTg-AD mice subjected to metabolic challenge with a high fat diet. In the probiotic group, there was less deterioration in novel object recognition and hippocampal neuronal spine density over the duration of the study compared to the control group. These changes were accompanied by localised (brain) and systemic anti-inflammatory responses together with the prevention of diet induced weight gain and hypercholesterolemia and the modulation of liver function in the probiotic group. Compositional differences between the faecal microbiotas included lowering of the obesity-associated Firmicutes:Bacteriodetes ratio and reductions in the numbers of viable yeast in the probiotic group. The results illustrate the potential of the Lab4b probiotic as a neuroprotective agent and encourage further studies with human participants.